Respuesta :

The fraction as an expression using a negative exponent other than -1.

[tex]\frac{1}{15^{6}}[/tex] is [tex]15^{-6}[/tex] . correct option B.

Step-by-step explanation:

We have the following steps to write the fraction as an expression using a negative exponent other than -1   [tex]\frac{1}{15^{6}}[/tex] .

⇒ [tex]\frac{1}{15^{6}}[/tex]

⇒ [tex]\frac{(1)^{6}}{(15)^{6}}[/tex]

⇒ [tex](\frac{1}{15})^{6}[/tex]

⇒ [tex](\frac{1}{15})^{6} (\frac{15}{15})^{-6}[/tex]

⇒ [tex](\frac{(15)^{-6}}{(15)^{6-6}})[/tex]

⇒ [tex]\frac{15^{-6}}{15^{0}}[/tex]

⇒ [tex]\frac{(15)^{-6}}{1}[/tex]

⇒ [tex]15^{-6}[/tex]

The fraction as an expression using a negative exponent other than -1.

[tex]\frac{1}{15^{6}}[/tex] is [tex]15^{-6}[/tex] .